Optimization of protein yields in water extracts of Jackiopsis ornata roots by response surface methodology using microwave assisted extraction (MAE) - Elhag, Husam Eldin Elhag Abugabr; Nailaa, Aishath; Azilah, Ajit; W. F. W., Ishak; A. Z., Sulaiman; Badhrulhisham, Abdul Aziz; Prasad, D. M. Reddy (AIP Publishing, 2019)
Optimization of protein yields in water extracts that were obtained from Jackiopsis ornataroots by Microwave assisted extraction (MAE) was established by a Circumscribed Central Composite Design (CCCD). MAE proved to be an optimum choice for the protein extraction. The highest yield (20.425±108) was obtained with the parameters liquid to solid ratio (S= 30:1), particle size (P=0.022±0.002mm (radius), temperature (T= 65°C); microwave power (W= 300W) and extraction time (t= 20 minutes). Statistical analysis illustrated the adequacy of the generated full quadratic equation with ad high values of the coefficient of determination (R2), adjusted coefficient of determination R2adj and predicted coefficient p of determination R2pred The p value of the Lack of Fit test illustrated the adequacy of the model. The optimization conditions of extracting the protein was predicted to be with the parameters S: 26, P: 0.0284; T: 65 °C; P: 303 W and t: 20 min. The high efficiency of MAE to obtain J. ornataprotein extract encouraged further application on pilot and industrial scale.